Equity Leadership for English Learners During COVID-19: Early Lessons - Lavadenz, Magaly; Kaminski, Linda R. G.; Armas, Elvira G.; López, Grecya V. (Frontiers in Education, 2021)
This article provides the findings of an exploratory, qualitative study on distance learning policies and practices from a purposeful sample of five California school districts and 25 district and school leaders with large numbers and/or larger percentages of current or former English Learners. To understand the extent to which leaders address English Learners’/Emergent Bilinguals’ (EL/EM) needs during the pandemic, we posed the following research question: What are leaders’ local policies and practices in designing and implementing distance learning to promote equity for English Learners? We gathered three key district policy documents across three moments during the pandemic: 1) COVID –19 Operations Written Reports (Spring 2020), School Reopening Plans (Summer 2020), and Learning Continuity and Attendance Plans (Fall 2020). We also conducted interviews and triangulated data sources using grounded theory to analyze and understand how equity is framed and implemented. Data triangulation and iterative rounds of coding allowed us to identify three inter-related themes: 1) leading in the crisis of connectivity and bridging the digital divide; 2) maximizing diverse ELs’ learning experiences; and, 3) building from collaborative leadership cultures to collaborative virtual leadership cultures. Using these key findings, we conceptualized the Framework for Equity Leadership for English Learners to address the needs of this underserved population. We conclude with a call for further examination, in both leadership preparation as well as in policy implementation research.